Fexofenadine Overcomes Osimertinib Resistance by Inhibiting c‐Met in Non‐Small Cell Lung Cancer - Kenneth K. W. To; Kwong‐Sak Leung; William C. Cho (MedComm – Oncology)
ABSTRACT Osimertinib is the only third‐generation EGFR tyrosine kinase inhibitor clinically approved for first‐line treatment of advanced NSCLC patients harboring EGFR mutations. However, drug resistance severely hinders its clinical efficacy. Acquired MET amplification is an important mechanism causing osimertinib resistance. This study is the first to identify fexofenadine, originally indicated for allergic rhinitis and chronic urticaria, as a putative Met‐inhibitor by in silico chemical‐protein interactome analysis of known Met inhibitors. Fexofenadine was verified to inhibit recombinant Met kinase in cell‐free assay and phosphorylation of Met and other downstream signaling molecules in osimertinib‐resistant NSCLC cell lines. KINOME profiling revealed a similar kinase inhibition profile between fexofenadine and a known Met‐inhibiting drug cabozantinib using Spearman rank‐order correlation analysis. Among the tested osimertinib‐resistant NSCLC cell lines, fexofenadine was the most efficacious in potentiating osimertinib in NCI‐H820 (having MET amplification and EGFR‐T790M mutation). Transcriptome profiling in NCI‐H820 revealed that the differentially expressed genes following fexofenadine treatment were enriched in epithelial‐mesenchymal transition‐related biological pathways. Importantly, fexofenadine was also shown to significantly potentiate the antitumor effect of osimertinib in a drug‐refractory NSCLC patient‐derived tumor xenograft model in NSG mice, without inducing notable adverse effects. These findings advocate the clinical evaluation of repurposing fexofenadine to overcome osimertinib resistance.